Erythropoietin: from erythropoiesis to cardioprotection - Liermis Michael Dita Salabert; Ivis Mendoza Hernández; Rafael Alejandro Gómez Baute; Elena García López; Lázaro E. de la Cruz Avilés; Aramis Núñez Quintana (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Many of the drugs that has shown promise in the treatment of hematologic malignancies and solid tumors, associated with a high potential cardiotoxic. Within this group stand anthracyclines, identified as the type of chemotherapy most likely to cause heart damage, short or long term. With the improvement achieved in the survival of patients with these diseases, this adverse event has become a major concern for the scientific community. Although many agents have been evaluated as potential cardioprotective therapeutic, clinical data are limited and does not suggest that the use of these agents promotes the survival of patients undergoing cardiotoxic treatments. The identification of erythropoietin receptor in hematopoietic tissues, including the heart, as well as its marked cardioprotective effect during ischemia have led to the hypothesis that erythropoietin may be able to prevent anthracycline-induced cardiomyopathy. Addressing this hypothesis is the objective of this work.